Tax reforms and equity in ACP countries - Manfred Holthus; Rasul Shams (Intereconomics, 1994)
While the tax reforms which have been instituted as part of the Structural Adjustment Programmes in ACP countries primarily aim at simplifying tax systems and raising their efficiency, they are also intended to improve distributional equity. This article assesses the equity effects of taxation policies in two selected ACP countries and points out what scope still exists for taxation measures to improve distributional equity without impairing allocative efficiency.
Keywords: 330; Fiscal Policy